2021
DOI: 10.1101/2021.05.11.21256917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methotrexate Hampers Immunogenicity to BNT162b2 mRNA COVID-19 Vaccine in Immune-Mediated Inflammatory Disease

Abstract: Objective: To investigate the humoral and cellular immune response to mRNA COVID-19 vaccines in patients with immune-mediated inflammatory diseases (IMIDs) on immunomodulatory treatment. Methods: Established patients at NYU Langone Health with IMID (n=51) receiving the BNT162b2 mRNA vaccination were assessed at baseline and after second immunization. Healthy subjects served as controls (n=26). IgG antibody responses to the spike protein were analyzed for humoral response. Cellular immune response to SARS-Co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 21 publications
5
87
3
2
Order By: Relevance
“…Consistent with this, our Spike antibody avidity experiments demonstrate progressive maturation of serum antibodies following mRNA vaccination, with increasing avidity through at least a month post second vaccination. However, much remains to be learned about Tfh responses in this context and whether these cells play a role in poor antibody responses after mRNA vaccination (61) . Two prior studies evaluated mRNA vaccination for influenza in humans and non-human primates and found robust induction of ICOS + CXCR3 + PD-1 + cTfh responses and neutralizing antibodies (48, 62) .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, our Spike antibody avidity experiments demonstrate progressive maturation of serum antibodies following mRNA vaccination, with increasing avidity through at least a month post second vaccination. However, much remains to be learned about Tfh responses in this context and whether these cells play a role in poor antibody responses after mRNA vaccination (61) . Two prior studies evaluated mRNA vaccination for influenza in humans and non-human primates and found robust induction of ICOS + CXCR3 + PD-1 + cTfh responses and neutralizing antibodies (48, 62) .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas SARS-CoV-2 mRNA-based vaccination has been successful in generating robust B cell and T cell mediated vaccine responses in healthy individuals 44,45,47,48,50,51 , less is known about responses to these vaccines in patients with autoimmune conditions, particularly those receiving immunosuppressive or immune cell-depleting agents 29,52 . To examine the impact of anti-CD20 (aCD20) monoclonal antibody therapy on responses to SARS-CoV-2 mRNA vaccination, we recruited 20 patients with multiple sclerosis (MS) treated with aCD20 (MS-aCD20) and compared their vaccine-induced immune responses to 10 healthy control (HC) subjects within the University of Pennsylvania Health System (Extended Data Table 1).…”
Section: Impact Of Acd20 Therapy On Sars-cov-2 Mrna Vaccine-induced Antibody Responsesmentioning
confidence: 99%
“…1 2 Some common rheumatic and musculoskeletal disease (RMD) medications have been highlighted as possible influential factors on immunogenicity, particularly rituximab (RTX), mycophenolate mofetil (MMF), methotrexate (MTX), abatacept and glucocorticoids. [3][4][5][6][7] The European Alliance of Associations for Rheumatology (EULAR) launched a COVID-19 registry in March 2020, capturing COVID-19 outcomes in the European RMD population. Questions on reinfection and vaccination were added in January 2021.…”
Section: Sars-cov-2 Infection After Vaccination In Patients With Inflammatory Rheumatic and Musculoskeletal Diseasesmentioning
confidence: 99%